Pengaruh Lingkungan Kerja Fisik Dan Fasilitas Kerja Terhadap Efektivitas Kerja Pegawai Di BKPSDM Kota Surakarta - Syafika Aliya; Wiedy Murtini; Nur Rahmi Akbarini (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to determine (1) the impact of the physical work environment on employee effectiveness, (2) the impact of work facilities on employee effectiveness, and (3) the combined impact of the physical work environment and work facilities on employee effectiveness. The research was conducted at the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Surakarta. This research uses a quantitative descriptive correlation method, which is used to explain the phenomena under study using numbers or measurable data. The sampling technique used in this study is Non Probability Sampling. The sample size consisted of 47 employees from Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Surakarta. The data collection technique employed in this study involves the utilization of questionnaires/surveys, with the Likert scale employed as the measurement scale. The collected data will be subjected to analysis using multiple linear regression.The results of this study indicate that (1) there is a significant impact of the physical work environment on employee effectiveness with (tcount 2.931 > ttable 2.01537), (2) there is a significant impact of work facilities on employee effectiveness with (tcount 2.744 > ttable 2.01537). Furthermore, there is a significant combined impact of the physical work environment (X1) and work facilities (X2) on employee effectiveness (Y) with an (Fcount 11.395 > Ftable of 3.20).